2010
DOI: 10.2527/jas.2009-2676
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, maternal, and environmental variance components for body weight and length of Atlantic cod at 2 points in life1

Abstract: Variance components were estimated for 2 body size traits of Atlantic cod at 2 time points. Wild-caught founders from 3 regions off eastern North America were spawned and their progeny were reared at 2 locations in 2 consecutive years. Full-sib families (n = 148) were kept separate until individuals achieved a size large enough to be tagged. At that time (220 d of age), BW and length of 47,637 offspring from 90 sires and 89 dams were recorded. The juveniles were then transferred to sea cages at 3 sites, where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 19 publications
3
15
0
Order By: Relevance
“…Despite neither study evaluating the importance of including c 2 , both did show a trend towards its decreasing importance as the fish become older, similar to our results. A trend of decreasing importance of family effect when increasing the age has been observed in other fish as well(Tosh et al, 2010).…”
mentioning
confidence: 87%
“…Despite neither study evaluating the importance of including c 2 , both did show a trend towards its decreasing importance as the fish become older, similar to our results. A trend of decreasing importance of family effect when increasing the age has been observed in other fish as well(Tosh et al, 2010).…”
mentioning
confidence: 87%
“…However, most mortality occurs over the period we measured. One study showed that, in relation to maternal effects on larval body size of cod, variation seen in juveniles was still apparent in offspring nearing 2 yr old (Tosh et al 2010). Another study used otolith backcalculations to determine that fast-growing larvae had better chances of survival in the long term (Campana 1996).…”
Section: Discussionmentioning
confidence: 99%
“…However in other experimental designs where c 2 is present genetic variances tend to be overestimated when c 2 has been unaccounted in statistical models (Tosh et al, 2010). Dupont-Nivet et al (2009) went to the extent of creating maternal clones for genetic variance component assessment to minimise maternal effects.…”
Section: Discussionmentioning
confidence: 99%
“…In some fish species the maternal common environmental effect (c 2 ) for growth can be as high as 0.21 Khaw et al (2009) but are generally below 0.10 ( Dupont-Nivet et al, 2010;Doupe, 2004;Gall and Huang, 1988). Even with estimates below 0.10, omitting maternal or family components can substantially inflate heritability estimates (Tosh et al, 2010;Winkelman and Peterson, 1994). The confounding of common environmental effects with additive genetic effects is a particular problem when only one generation of performance measurements is available.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%